CDw149 antibodies recognize a clustered subset of CD47 molecules associated with cytoplasmic signaling molecules - Drbal, K; Cerný, J; Angelisová, P; Hilgert, I; Cebecauer, M; Sinkora, J; Horejsí, V (Tissue antigens, 2000)
One of the recently described antigens broadly expressed on human leukocytes is CDw149, which was defined at the 6th Human Leukocyte Differentiation Antigen (HLDA) Workshop by means of 2 monoclonal antibodies (mAbs). Molecular characterization of this antigen has been lacking. In the present study we demonstrate that these anti-CDw149 mAbs actually recognize a clustered subset of a well-defined membrane protein, CD47, also known as integrin-associated protein (IAP). This clustered subset is present on leukocytes but not erythrocytes. The anti-CDw149 mAbs bind with only low affinity to a monomeric (unclustered) subset of CD47 but with high avidity to the CD47 clusters. A fraction of CD47 is associated with large complexes containing cytoplasmic signaling molecules (Src family kinases and heterotrimeric G-proteins) similar to glycosphingolipid-enriched microdomains (GEMs), which may explain the previously described signaling capacity of CD47. The low-affinity anti-CD47 mAbs may be useful tools targeting specific receptor complexes involved in cell activation. Specific reactivity of low-affinity mAbs with clustered subsets of cell surface antigens may more generally explain the nature of poorly defined "activation forms" or activation neoepitopes described previously for several cell surface molecules.
Keywords: kinetika; kvarterní struktura proteinů; Antibody Affinity; membránové proteiny; signální transdukce; Cell Line; Leukocytes; afinita protilátek; Jurkat buňky; Membrane Proteins; Carrier Proteins; monoklonální protilátky; Signal Transduction; Antibodies, Monoclonal; Protein Structure, Quaternary; antigeny CD47; Erythrocytes; cytoplazma; erytrocyty; Humans; Macromolecular Substances; CD47 Antigen; Antigens, CD; makromolekulární látky; Jurkat Cells; Kinetics; buněčné linie; Cytoplasm; leukocyty; transportní proteiny; CD antigeny; lidé